2016
DOI: 10.1016/j.addr.2015.09.012
|View full text |Cite
|
Sign up to set email alerts
|

PEGylation as a strategy for improving nanoparticle-based drug and gene delivery

Abstract: Coating the surface of nanoparticles with polyethylene glycol (PEG), or “PEGylation”, is a commonly used approach for improving the efficiency of drug and gene delivery to target cells and tissues. Building from the success of PEGylating proteins to improve systemic circulation time and decrease immunogenicity, the impact of PEG coatings on the fate of systemically administered nanoparticle formulations has, and continues to be, widely studied. PEG coatings on nanoparticles shield the surface from aggregation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
2,233
1
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 3,168 publications
(2,289 citation statements)
references
References 240 publications
(405 reference statements)
41
2,233
1
14
Order By: Relevance
“…To overcome this biological barrier caused by some novel inhalation pharmaceuticals, functionalized and nontoxic nanocarriers can be used. Inspired from viruses, nanosized particles with neutrally charged coatings such as polyethylene glycol (PEG) can efficiently penetrate the mucus layer in contrast to charged particles (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this biological barrier caused by some novel inhalation pharmaceuticals, functionalized and nontoxic nanocarriers can be used. Inspired from viruses, nanosized particles with neutrally charged coatings such as polyethylene glycol (PEG) can efficiently penetrate the mucus layer in contrast to charged particles (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has also been reported that PLGA/PEG nanoparticles can penetrate and diffuse through mucus-based layers due to the PEG properties, improving the drug delivery in the gastrointestinal or cervicovaginal tract, among others. [123] Cu and co-workers demonstrated an improvement in drug diffusion when PLGA/PEG nanoparticles penetrated the human cervical mucus into the vaginal tissue. [124] Indeed, Justin Hanes' research group proved that high densities of PEG in the surface of PLGA nanoparticles imply less interactions between mucins and nanoparticles, hence leading to a mucopenetrating profile of the nanosystem and facilitating its transport in human cervicovaginal mucus.…”
Section: Poly(lactic-co-glycolic) Acid Nanoparticlesmentioning
confidence: 99%
“…PEGylation has been widely used for the surface coating of the nanoparticles in order to introduce a stealth property to the nanoparticles, because PEG chains hinder the non-specific interaction of the nanoparticle's surface with the blood components due to tight hydrated layer and reduce MPS recognition, resulting in reduced uptake and clearance from the bloodstream. [39] PEGylation of liposomes have shown to extended the blood circulation time from less than 30 min to 5 h after systemically administration, conferring the 'stealth effect' of PEGylation. [40] Similarly, PEGylated poly(lacticco-glycolic acid) (PLGA) nanoparticles have shown to significantly increased the blood circulation half-life together with reduced liver uptake, compared to non-PEGylated PLGA nanoparticles.…”
Section: First Generation Nanomedicinesmentioning
confidence: 99%